Analisis Penerimaan, Penempatan serta Promosi Jabatan Karyawan Pada PT. Bank Syari’ah Indonesia Kantor Cabang Pembantu Muara Bulian - Nadiatul Khoiroh; Ratna Ratna; Dian Pratiwi (CITRA EKONOMI, 2021)
The purpose of this study was to analyze the leadership style in the process of accepting, placing and promoting employees at the Indonesian Islamic bank branch office Muara Bulian. Where the method used is qualitative with data collection in this study used observation, interviews and documentation with data analysis techniques used data reduction, data presentation and conclusions.Based on the results of this study, it can be explained that in the process of hiring employees using a closed method which prioritizes employees from internal sources, in the placement of employees based on the needs of work positions and abilities or expertise possessed, then promotion of employees is seen on the basis of experience and skills of employees and also comply with the conditions that have been determined.